Mathematical models of the Earth’s density structure and their applications in gravimetric forward modeling - TENZER, Robert (Contributions to Geophysics and Geodesy, 2015)
A generalized mathematical model of the Earth’s density structure is presented in this study. This model is defined based on applying the spectral expressions for a 3-D density distribution within the arbitrary volumetric mass layers. The 3-D density model is then converted into a form which describes the Earth’s density structure by means of the density-contrast interfaces between the volumetric mass layers while additional correction terms are applied to account for radial density changes. The applied numerical schemes utilize methods for a spherical harmonic analysis and synthesis of the global density structure models. The developed the Earth’s density models are then defined in terms of the spherical density and density-contrast functions. We also demonstrate how these Earth’s density models can be applied in the gravimetric forward modeling and discuss some practical aspects of representing mathematically density structures within particular components of the Earth’s interior.